Global per capita CO2 emissions - stable in the long run? - Bjart Holtsmark (Statistics Norway, Research Department, 2005)
Global per capita CO2 emissions have been relatively stable during the last decades. It has been suggested that the Intergovernmental Panel on Climate Change (IPCC) and its scenario makers have ignored this stability. This paper presents a simple analytical framework explaining generally the stability of global per capita CO2 emissions during the last decades. The same analytical framework, supported by numerical illustrations, indicates that this stability is unlikely to persist and that current trends in regional per capita emissions are in close agreement with the IPCC scenarios
Keywords: Q30; Q41; 330; Global carbon emissions; SRES; IPCC; scenarios.